Investigation of Time and Energy Consumption using the Physical Model - Baums, A.; Gordjusins, A.; Kanonirs, G. (Elektronika ir Elektrotechnika, 2011)
Different machine vision, image analysis systems and navigation sensor modules were tested during the physical model development, the most conformable was selected. Different route planning algorithms were implemented and analyzed. The best result is obtained using the Ant-colony algorithm. The physical model is used for an autonomous outdoor mobile robot software development and student education. Ill. 3, bibl. 5 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.363